Economic Activity of the Individual and the Evaluation of Motivation - Lydeka, Zigmas (Ekonomika, 1997)
The article analyses the concept of an individual’s economic activity and its motivational evolution in different economic systems. The purpose of economic activity is to obtain certain real values that satisfy appropriate requirements or to ensure that these requirements are satisfied. This process is determined by two essential circumstances: motivation and economic environment of economic activity. An absolute necessity is the motivational desire to overcome inadequacy between limitless requirements and limited possibilities in order to satisfy the fulfillment of economic activities. The main motive of an individual’s economic activity execution is to guarantee its existence and continuity and to satisfy various requirements as well as to create conditions for them. The motive of economic activity obviously forces the participant to either increase his/her possibilities of activity creating new conditions to satisfy, or limit the requirements by decreasing the scope of usage.The philosophical motives of activities are directly aimed at an individual in one direction. Meanwhile, political forces after the participants from both directions. Economic leverage is aimed not at the economic participants. but from them to the environment in the opposite direction.